Spawning interactions between hatchery‐reared and wild naturalized rainbow trout (Oncorhynchus mykiss, Walbaum, 1792) in high‐altitude tropical streams, Kenya - Justus N. Njue; Charles C. Ngugi; Mucai Muchiri; Mary A. Opiyo (Aquaculture, Fish and Fisheries, 2024)
Abstract Rainbow trout (Oncorhynchus mykiss) is among the most widely translocated fish species in the world. The current study evaluated the spawning interactions between naturalized and wild rainbow trout from two high‐altitude second‐order streams, in Kenya. Data on total length, weight, condition factor, fecundity, fertilization, egg diameter and fry survival were collected on spawning rainbow trout between March and December 2021. Length–weight relationship showed parabolic equations as W = 0.0144L2.900, W = 0.0069L3.0285 and W = 0.00027L3.175 for wild fish stock, hatchery‐reared and wild × hatchery‐reared rainbow trout, respectively. Total fecundity differed significantly among the hatchery‐reared, wild fish and the cross of the two (p < 0.05). The fertilization rate showed significant differences (p < 0.05), with no discernable difference observed between the hatchery‐reared and crossed (wild × hatchery‐reared). There was a positive correlation among the total fecundity to female egg weight, female body weight, fertilization rate and eyed egg survival in all the populations. Relative fecundity was significantly different among the three groups of fish (p < 0.05), but the differences between the hatchery and the crossed (wild × hatchery‐reared) fish showed no significant differences. We recommend the use of crossed (wild × hatchery‐reared) populations for fry production for use in aquaculture as they presented the highest fecundity and gave the best outcome of fry with high survival.